2022
DOI: 10.1002/chem.202201175
|View full text |Cite
|
Sign up to set email alerts
|

Online Reaction Monitoring with Fast and Flow‐Compatible Diffusion NMR Spectroscopy

Abstract: Online monitoring by flow NMR spectroscopy is a powerful approach to study chemical reactions and processes, which can provide mechanistic understanding, and drive optimisations. However, some of the most useful methods for mixture analysis and reaction monitoring are not directly applicable in flow conditions. This is the case of classic diffusion‐ordered NMR spectroscopy (DOSY) methods, which can be used to separate the spectral information for mixture's components. We describe a fast and flow‐compatible dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…152 Very recently, two other fast and flow compatible diffusion experiments were also developed and applied to the monitoring of organic reactions. 153,154…”
Section: Fast 2d Nmr Methodsmentioning
confidence: 99%
“…152 Very recently, two other fast and flow compatible diffusion experiments were also developed and applied to the monitoring of organic reactions. 153,154…”
Section: Fast 2d Nmr Methodsmentioning
confidence: 99%
“…Marchand et al recently showed that, using a convection compensated pulse sequences, and a diffusion-encoding axis that is orthogonal to the main direction of the flow, accurate diffusion coefficients can be measured for samples flowing at up to 3 mL min −1 . 199 In addition, they showed that the use of multiple orthogonal axes in convection-compensated diffusion NMR pulse sequences also made it possible to reduce the number of scans to just one per value of the diffusion-encoding gradient. This “one-shot” implementation makes it possible to collect a complete data set in less than 90 s, thus giving a useful tool for reaction monitoring application, as illustrated in Fig.…”
Section: Conditions Of Operationmentioning
confidence: 99%
“…This approach is used for applications ranging from authentication 14,15 to reaction monitoring. 16,17 The measurement of diffusion coefficients by NMR is based on the application of a pair of magnetic field gradient pulses, separated by a delay. Diffusion during the delay results in an attenuation of the NMR signals.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] The accurate measurement of diffusion coefficients for a sample in continuous flow is also particularly challenging. 17,29 The effect of flow on conventional diffusion NMR and MRI is well studied theoretically and experimentally. [31][32][33][34][35][36][37][38][39][40] Notably, it can be shown that a constant velocity flow results in an additional phase shift of the magnetization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation